آليات تقييم الصيرفة الاسلامية في البنوك التجارية وتحدياتها -دراسة حالة البنك الوطني الجزائري - ساعد, بن; الحميد, عبد (Ibn Khaldun University of Tiaret, 2022)
يعتبر النظام المصرفي من بين الأسس التي يعتمد عليها النشاط الاقتصادي لأي مجتمع و ذلك بالنظر لأهمية الدور الذي يلعبه في المساهمة في إمداد النشاط الاقتصادي بالأموال، اللازمة من اجل تنميته و تطوي ره ، وقد اجمع الباحثون الاقتصاديون على أن من بين أسباب الأزمات المالية ترجع إلى الأسلوب الربوي المتبع من طرف البنوك التقليدية، خصوصا بعد أن ضربت الأزمة المالية العالمية عصب الاقتصاد الرأسمالي سنة 2008 وهزت اقتصاديات الدول وأضعفت البنوك التجارية خلافا عن البنوك الإسلامية والبنوك التجارية ذات الشبابيك الإسلامية ، ومن هذا المنطلق ازدادت الحاجة إلى وجود بنوك تعمل وفقا للشريعة الإسلامية والتي تقوم على أساس إلغاء الفائدة وعدم التعامل بالربا في تعاملاتها، ومنه فقد أصبحت هذه البنوك لاعبا مؤثرا وبارزا في اقتصاديات الدول الإسلامية و العالمية و التي من بينها الجزائر التي اتجهت هي الأخرى للدخول إلى عالم الصیرفة الإسلامية باعتمادها لافتتاح نوافذ إسلامية على مستوى البنوك العمومية. ومن خلال دراستنا توصلنا الى أن البنوك العمومية الجزائرية تحاول خوض تجربة فتح شبابيك إسلامية وقد خلصنا بأن اعتماد هذه البنوك على آلية التعامل بشبابيك تعمل وفق قواعد الشريعة الإسلامية في معاملاتها المالية من شأنه أن يحقق استقطاب ورضا الزبائن. The banking system is considered one of the foundations on which the economic activity of any society is based, given the importance of the role, it plays in helping to supply economic activity with the funds necessary for its operation. Economic researchers have agreed that among the causes of financial crises are due to the usurious method adopted by banks, especially after the global financial crisis hit the backbone of the capitalist economy in 2008, shook the economies of the countries, and weakened commercial banks unlike Islamic banks and commercial banks with Islamic windows From this point of view, the need has grown for the existence of bank operating in accordance with Islamic law, which is based on the abolition of interests in their financial transactions, these banks have become an influential and leading actor in the economies of Islamic countries including Algeria, which has also tended to enter the Islamic banking world by adopting it to open Islamic windows at the level of public banks. Through our study, we concluded that Algerian public banks are trying to live with the opening of Islamic counters, and we concluded that the dependence of these banks on the processing mechanism of counters that operate according to the rules of Islamic Sharia law in their financial transactions, would attract and satisfy customers.
Keywords: Banques commerciales; Banques islamiques; Fenêtres islamiques; Satisfaction client; البنوك الإسلامية; البنوك التجارية; النوافذ الإسلامية; رضا الزبائن

Banks responsibility in the collection of the commercial paper contract - Al-Shawabkeh, Wa’ed (Al-Balqa Journal for Research and Studies, 2022)
The importance of studying this contract is to establish the legal nature of the bank’s responsibility when it fails to collect the value of the commercial paper, and to know the role and direction of the judiciary in that respect. The study relied on the element of analysis and education in a brief scientific way. The purpose of the study is to examine the legal basis for the Bank’s responsibility in the collection contract and the general provisions for this responsibility resulting for it, and to cover that responsibility in all its aspects. The study relies on the analytical method in order to achieve the purpose and objectives of the research, where the legal texts will be analyzed and practical results will be reached. In this research legal texts will be analyzed to reach scientific results, the study also reached results, including that there was no regulation from the Jordanian legislator for the collection, in addition to the overlapping of the agency and deposit contracts in the collection contract and that the bank’s responsibility towards its client is a contractual responsibility due to the nature of the relationship between them. The research recommends that the Jordanian Trade law should include special texts dealing with the collection contract, and that the judiciary be more present while evaluating the nature of the relationship and the basis of responsibility between the bank and its client, and it should be clearly stated that the bank may require the disqualification of itself from the liability resulting from collection contract.